2020
DOI: 10.3390/jcm9020323
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Proteomic Approach for Identification of Serum Biomarkers in Hepatocellular Carcinoma Patients with Normal AFP

Abstract: Alpha fetoprotein (AFP) has been used as a serologic indicator of hepatocellular carcinoma (HCC). We aimed to identify an HCC-specific serum biomarker for diagnosis using a multiplexed proteomic technique in HCC patients with normal AFP levels. A total of 152 patients were included from Guro Hospital, Korea University. Among 267 identified proteins, 28 and 86 proteins showed at least a two-fold elevation or reduction in expression, respectively. Multiple reaction monitoring (MRM) analysis of 41 proteins reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For example, Heo et al achieved specificity and sensitivity of around 80% for early diagnostic HCC marker EIF3A peptides from serum samples, and ELISA and western blotting validation confirmed the use of selected peptides clinically [100]. Similar to the previous study performed by Zhan's group [99], Lee's group also validated the presence of AFP in a large number of HCC patients' serum samples and verified AFP expression by using RT-qPCR and western blotting techniques [101]. Furthermore, another study revealed that AFP along with heptoglobin specific N-glycopeptides may achieve a sensitivity of greater than 80% as diagnostic biomarkers for nonalcoholic steatohepatitis HCC patients [102].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 59%
“…For example, Heo et al achieved specificity and sensitivity of around 80% for early diagnostic HCC marker EIF3A peptides from serum samples, and ELISA and western blotting validation confirmed the use of selected peptides clinically [100]. Similar to the previous study performed by Zhan's group [99], Lee's group also validated the presence of AFP in a large number of HCC patients' serum samples and verified AFP expression by using RT-qPCR and western blotting techniques [101]. Furthermore, another study revealed that AFP along with heptoglobin specific N-glycopeptides may achieve a sensitivity of greater than 80% as diagnostic biomarkers for nonalcoholic steatohepatitis HCC patients [102].…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 59%
“…No study that has aimed to identify new HCC serum markers through mass spectrometry has validated the discriminatory performance of the identified markers in a chronologically separately collected, multicenter cohort. The current study is also distinct from a previous report by our group, in that data preprocessing was adopted before the selection of the markers and that fewer markers were involved in the developed panel.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, Ultrasonography and AFP detection are commonly accepted as useful methods to periodically screen HCC (17)(18)(19). Imaging diagnosis of early HCC still remains some troubles, and serum AFP has a nonnegligible false negative rate of about 30%, which could potentially lead to misdiagnosis, missed diagnosis, and a delay in timely treatment (20)(21)(22). Therefore, we planned to analyze whether LINC00485 can help clinicians better distinguish HCC patients.…”
Section: Discussionmentioning
confidence: 99%